Manajemen Risiko Produksi Sayuran Sistem Organik di PT Tanikota Agribudaya Edulestari - Suroso, Muhammad Naufal Adiya; Supyandi, Dika (Universitas Galuh, 2024)
The production of organic vegetables at PT Tanikota Agribudaya Edulestari (TABEL) is enclave in nature as it is carried out in the midst of urban areas, making it susceptible to risks. This has led to low production yields, and the company has not been able to achieve its targets. This research is a qualitative research with a case study approach. The data analysis method used in this research is the House of Risk (HOR). The aim is to identify risk events and risk sources that exist in the organic vegetable production stage at PT TABEL, and formulate control actions to reduce these risks. Based on the results of the study, there are 18 risk events with 16 risk sources that cause them. There are 6 risk sources that are prioritized, namely pest attacks, erratic weather, disease attacks, weeds, no clear SOPs for employees, low employee competence. To overcome these risk sources, 8 control actions were formulated, sorted by priority, namely providing training and professional certification for garden employees, making effective vegetable pesticide concoctions, routine monitoring of pests and diseases, building simple plant protection roofs, implementing intercropping systems, creating and establishing clear SOPs for employees, thorough use of mulch, more regular recording and scheduling.